An accurate physical knowledge‐based model for behavioral modeling and digital predistortion of power amplifiers. Issue 6 (20th November 2012) - Du, Tianjiao; Yu, Cuiping; Gao, Jinchun; Liu, Yuanan; Li, Shulan; Wu, Yongle
<x xml:space="preserve">Abstract</x> The objective of this article is to present an accurate model for behavioral modeling and digital predistortion of power amplifiers (PAs) using physical knowledge. Starting with the physically meaningful block model, we present a novel approach to simplify the block model and propose a simplified physical knowledge‐based (SPK) model. The SPK model's performance was experimentally assessed by two types of PAs (a LDMOS Doherty PA and a GaN Doherty PA) and two signals (a single carrier 16QAM signal and a 2‐carrier WCDMA signal). All experimental results prove the superiority of the SPK model. Compared with the 1st‐dynamic deviation reduction (DDR) approach and the 2nd‐simplified DDR approach, the SPK approach achieves average ACPR improvements of 4.4 dB and 2.5 dB, respectively. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE 23: 682–689, 2013.